Insights Into the MYB-Related Transcription Factors Involved in Regulating Floral Aroma Synthesis in Sweet Osmanthus - Yan, Xin; Ding, Wenjie; Wu, Xiuyi; Wang, Lianggui; Yang, Xiulian; Yue, Yuanzheng (Frontiers in Plant Science, 2022)
As an important member of the MYB transcription factor (TF) family, the MYB-related TFs play multiple roles in regulating the synthesis of secondary metabolites and developmental processes, as well as in response to numerous biotic and abiotic stressors in plants. However, little is known regarding their roles in regulating the formation of floral volatile organic compounds (VOCs). In this study, we conducted a genome-wide analysis of MYB-related proteins in sweet osmanthus; 212 OfMYB-related TFs were divided into three distinct subgroups based on the phylogenetic analysis. Additionally, we found that the expansion of the OfMYB-related genes occurred primarily through segmental duplication events, and purifying selection occurred in all duplicated gene pairs. RNA-seq data revealed that the OfMYB-related genes were widely expressed in different organs of sweet osmanthus, and some showed flower organ/development stage-preferential expression patterns. Here, three OfMYB-related genes (OfMYB1R70/114/201), which were expressed nuclearly in floral organs, were found to be significantly involved in regulating the synthesis of floral VOCs. Only, OfMYB1R201 had transcriptional activity, thus implying that this gene participates in regulating the expression of VOC synthesis related genes. Remarkably, the transient expression results suggested that OfMYB1R70, OfMYB1R114, and OfMYB1R201 are involved in the regulation of VOC synthesis; OfMYB1R114 and OfMYB1R70 are involved in accelerating β-ionone formation. In contrast, OfMYB1R201 decreases the synthesis of β-ionone. Our results deepen our knowledge of the functions of MYB-related TFs and provide critical candidate genes for the floral aroma breeding of sweet osmanthus in the future.